Comparative analysis of the testes and spermatogenesis in species of the family Pentatomidae (Heteroptera) - de Souza, Hederson Vinicius [UNESP]; Murakami, Aline Sumitani [UNESP]; de Moura, Juliana [UNESP]; de Almeida, Elisangela Cristiane [UNESP]; Gallego Marques, Inaia Fernandes [UNESP]; Itoyama, Mary Massumi [UNESP] (Czech Acad Sci, Inst Entomology, 2011)
There are few studies on the morphology and meiosis in the testicles of Heteroptera, but are extremely important, especially for the family Pentatomidae, because in some species in this family meiosis in the testicular lobes results in the production of non-fertile spermatozoa. With the aim of improving the level of understanding of this phenomenon the morphology of the testes and spermatogenesis in 10 species of Pentatomidae were recorded and compared. All of them have testes covered by a pigmented peritoneal sheath. In some species the internal membrane or just inside the peritoneal sheath is pigmented. The pigmentation of both membranes varied. The pigmentation of both was either yellow, or the internal membrane was yellowish and the external one reddish. When the membrane is pigmented, the colour is red or yellow. The number of lobes varied from 3 to 7, with intermediate numbers of 4 and 6. The size and diameter of the lobes are similar in all the species studied, except Proxys albopunculatus, in which the diameter of the third and fifth is smaller than that of the other lobes. The behaviour of the cells during spermatogenesis was the same in all lobes of most species, except in P. albopunctulatus, in which the harlequin lobe is absent and the cells in lobes 4 and 6 exhibited characteristics different from those of cells in lobes 1-3 and 5. Chlorocoris complanatus and Loxa deducta (both Pentatominae) have a harlequin lobe (lobe 5). The chromosome complements recorded were: 2n = 12 (10A + XY) in Dichelops melacanthus and Edessa collaris, 2n = 14 (12A + XY) in C. complanatus, Edessa meditabunda, Ladeaschistus sp., Loxa deducta, P. albopunctulatus, Piezodorus guildinii and Thyanta perditor and 2n = 16 (14A + XY) in Edessa affinis. Thus, this study extends the knowledge of characteristics, such as the pigmentation of the peritoneal sheath, number of testicular lobes, the occurrence of meiotic cells in some testicular lobes, and the chromosome complements of the family Pentatomidae.
Keywords: Pentatomidae; harlequin lobe; meiosis; spermatogenesis; spermiogenesis